FEASIBILITY STUDY OF MICRO-LATTICE STRUCTURES BY MULTIPHOTON LITHOGRAPHY - Markus Wimmer; Zoltan Major (Acta Polytechnica CTU Proceedings)
The paper describes the possibilities of additive manufacturing with multiphoton lithography. The basis of this technology is that a laser beam (with a certain wavelength) is ﬁred into the mixture of a monomer and a photo-initiator. When the energy of the laser is high enough, the latter acts as a catalyser for the polymerization of the monomer compound. This study focuses on the inﬂuences of certain parameters of the multiphoton lithography process. One of the important aspects is the choice of the solvent for the post processing. In sequence to the solvent problem, the inﬂuence of the layer height is examined. Furthermore the limits and possibilities of the setup in use are investigated. As an example the diﬀerences in fabrication with the laser ﬁring with "constant frequency" and "constant density" were subject of this investigation. The second goal of the study was to compare three diﬀerent structures consisting of periodically repeating elements, scaled in size and number of elements per side.